Conhecimentos e práticas de cura dos distúrbios gastrointestinais no bairro São Sebastião, Abaetetuba, Pará, Brasil - PALHETA, Ivone Cardoso (2019)
In the Amazon, medicinal plants are the main resources for treatment of various human diseases such as gastrointestinal disorders. The present study aims to conduct an ethnobotanical study of medicinal plants used in the treatment of gastrointestinal disorders in São Sebastião, Abaetetuba, Pará, Brazil. We used the analysis of secondary databases collected from June 2013 to September 2014 when informal, open and semi-structured interviews with free listing of plants used to treat different human affections. Analyzes of all the mentioned species and their respective indications of use, being filtered to those used in the treatment of gastrointestinal disorders. The probabilistic sampling method was used and the selection of the home gardens to be visited was performed using the simple random sampling plan with the participation of 160 interlocutors. The qualitative approach was adopted to analyze the relationship of the residents with the home gardens plants. The Use Values (UVs) and Use Consensus Value (UCs) were calculated to assess the importance of the plants by the number of uses they presente. The residents come mainly from the rural communities abaetetubenses, where they worked in agriculture and continued the practice of cultivation in home gardens after migrating to the city. Were cited 53 species, distributed in 47 genera and 28 families, being Lamiaceae (15.09%) and Asteraceae (9.43%) the most representative. The most common form of preparation of the homemade recipes is the tea by decoction and the most used part of the plant is the leaf. The species with higher Use Values were Psidium guajava L. (UVs = 0.261) and Eleutherine bulbosa (Mill.) Urb. (UVs = 0.236), which are used in the treatment of diarrhea, amoebiasis, vomiting, bellyache and gastritis. The Use Consensus Value indicated a higher degree of agreement among the informants regarding the use of the species Kalanchoe pinnata (Lam.) Pers. (UCs = -0.575) and P. guajava (UCs = -0.450). It was observed that even in the urban environment the residents of the São Sebastião, whose majority is of rural origin, continue to exercise their therapeutic traditions through the plants.